Polymer dynamics from synthetic to biological macromolecules - Richter, Dieter; Biehl, Ralf; Monkenbusch, Michael; Hoffmann, Bernd; Merkel, Rudolf (Diffusion Fundamentals, 2007)
In soft materials entropic and enthalpic contributions are of similar magnitude and balance each other. Therefore, the macroscopic mechanical and rheological properties and the phase changes are determined to a high degree by thermal motion of the atoms and molecules. Most of the relevant dynamics takes place on mesoscopic length and time scales in between the picosecond atomic scale and the macroscopic frame. Allowing for the proper space time observation window, neutron spin echo (NSE) spectroscopy uniquely allows to address these motions. Here we briefly present some key experimental results on the mesoscopic dynamics of polymer systems, starting from the standard model of polymer motion - the Rouse model. We briefly touch the role of topological confinement as expressed in the reptation model and discuss in some more detail processes limiting the confinement. In the second part we touch on some new developments relating to large scale internal dynamics of proteins by neutron spin echo. We will report results of some pioneering studies which show the feasibility of such experiments on large scale protein motion which will most likely initiate further studies